The influence of full leg-length compression tights during treadmill running at race speed - McManus, C. J.; Butson, J.; Rogerson, M.; Waterworth, S.; Jones, B.; Cooper, C. E.; Sandercock, G. (International Journal of Sports Science & Coaching, 2022)
The aim of the present study was to examine whether full leg-length compression tights modify physiological and kinematic measures during treadmill running at a competitive race pace in moderately trained runners. Thirteen males and five females completed two 15-minute running tests at a speed corresponding to a recent race time wearing compression tights or loose-fitting running shorts. Running economy (RE) was determined by oxygen consumption and carbon dioxide expiration during the final 3 minutes of treadmill running. Muscle oxygenation, skin temperature, heart rate (HR), vertical oscillation, step frequency and ground contact time (GCT) were measured continuously. GCT was shorter with compression compared with control trials (p = 0.03), however, no differences in RE, muscle oxygenation, vertical oscillation, step frequency, HR or skin temperature were revealed. Despite a shorter GCT with compression tights, the findings suggest that moderately trained runners do not benefit nor limit physiological responses at a competitive race pace.